1987
DOI: 10.1016/0014-5793(87)80759-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ricin A chain in Escherichia coli

Abstract: DNA encoding ricin A chain was derived from preproricin cDNA and ligated into the expression vector pDS5/3. Transcription is controlled from the coliphage promoter P ~25 fused with the lac operator of E.coli. When induced, E.coZi 71.18 cells transformed with the recombinant plasmid express ricin A chain which is soluble and has full biological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 15 publications
3
38
0
Order By: Relevance
“…Initial efforts to express high levels of RTA in E. coli were complicated by temperature-dependent aggregation phenomena (29,30). RTA was stabilized in a previous study by fusion to P-galactosidase (25) and in the present study by fusion to glutathione-S-transferase.…”
Section: Discussionmentioning
confidence: 57%
“…Initial efforts to express high levels of RTA in E. coli were complicated by temperature-dependent aggregation phenomena (29,30). RTA was stabilized in a previous study by fusion to P-galactosidase (25) and in the present study by fusion to glutathione-S-transferase.…”
Section: Discussionmentioning
confidence: 57%
“…Previous attempts to express soluble, active RTA in E. coli have been complicated by temperature-dependent aggregation phenomena as well as minor alterations in RTA sequence (23,26). We have shown that RTA can be stabilized by fusion to P-galactosidase as described by Germino et al (7,8) and that soluble fusion protein is produced in high yield even in cultures grown at 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…The yeast expression system (6) yields very small amounts of RTA, which is difficult to purify from total yeast extracts. Available bacterial expression systems (23,26) produce material that is cumbersome to purify and may have solubility problems, especially at temperatures of 37°C or higher.…”
mentioning
confidence: 99%
“…Cloning and Expression of Recombinant Toxins-The vector pRICA, designed for expression of active RTA in the cytoplasm of Escherichia coli, has been described elsewhere (7). The RTA coding region with an additional 26 base pairs at the 5Ј-end is contained in an 873-base pair BamHI fragment.…”
Section: Methodsmentioning
confidence: 99%